Aspiration cytology of mammary analogue secretory carcinoma of the salivary gland. Issue 4 (4th August 2014) - Jung, Min Jung; Kim, Sang Yoon; Nam, Soon Yuhl; Roh, Jong‐Lyel; Choi, Seung‐Ho; Lee, Jeong Hyun; Baek, Jung Hwan; Cho, Kyung‐Ja
<x xml:space="preserve">Abstract</x> Background Aspiration cytologic findings of mammary analogue secretory carcinoma (MASC), a newly established salivary gland neoplasm defined by a t(12;15)(p13;q25) ETV6‐NTRK3 translocation, are not fully characterized to date. We report cytologic descriptions of nine cases of molecularly confirmed MASC, including two with unusual findings. Methods Aspiration smears from nine MASCs of the salivary glands were retrospectively reviewed and analyzed according to the cellular and structural features of the corresponding surgical specimens. Results Aspiration smears of MASC generally reflected the histologic diversity of the tumors. Among usual histologic findings, a micropapillary pattern was associated with a predominance of vacuolated individual cells on aspiration smears, a papillary‐cystic pattern with a predominance of thin branching papillary structures, and a microcystic pattern with a predominance of irregular sheets of eosinophilic cells. There were two unusual cases, one with three‐dimensional groups of high‐grade atypical cells, and one with epithelial clusters floating in a notably mucinous background. These cases represented MASC with high‐grade transformation and MASC with cystadenocarcinoma‐like features, respectively. The secretory activity of MASC was not prominent in the aspiration specimens. Conclusions Although unusual cases were present, most MASC cases showed characteristic cytologic findings, which could aid the cytologic diagnosis of MASC. And knowledge of the histologic spectrum of MASC, including high‐grade transformation, could be valuable for cytological differential diagnoses of salivary gland tumors, and the management of patients with MASC. Diagn. Cytopathol. 2015;43:287–293. © 2014 Wiley Periodicals, Inc.